Perovskite oxide and carbonate composite membrane for carbon dioxide transport - Zhuang, S.; Han, N.; Xing, M.; Meng, B.; Liu, Shaomin (Elsevier BV, 2019)
© 2018 Elsevier B.V. A novel La0.6Sr0.4Co0.2Fe0.8O3-d based ternary carbonate composite membrane was developed via melting impregnation. The enhanced carbon dioxide permeability is due to the existence of La0.6Sr0.4Co0.2Fe0.8O3-d, a mixed ionic-electronic conductor, and the carbonate phases. The composite membrane greatly promotes the CO2 surface reaction rate to form CO32- and the subsequent ionic transport rate. To further understand the mechanism, the effect of O2 on carbon dioxide permeability was also analyzed under fuel gas conditions.